Oncolytic vaccinia virus and cancer immunotherapy - Xu, Lihua; Sun, Huihui; Lemoine, Nicholas R.; Xuan, Yujing; Wang, Pengju (Frontiers in Immunology, 2024)
Oncolytic virotherapy (OVT) is a promising form of cancer treatment that uses genetically engineered viruses to replicate within cancer cells and trigger anti-tumor immune response. In addition to killing cancer cells, oncolytic viruses can also remodel the tumor microenvironment and stimulate a long-term anti-tumor immune response. Despite achieving positive results in cellular and organismal studies, there are currently only a few approved oncolytic viruses for clinical use.Vaccinia virus (VACV) has emerged as a potential candidate due to its ability to infect a wide range of cancer cells. This review discusses the mechanisms, benefits, and clinical trials of oncolytic VACVs. The safety and efficacy of different viral backbones are explored, as well as the effects of oncolytic VACVs on the tumor microenvironment. The potential combination of oncolytic VACVs with immunotherapy or traditional therapies is also highlighted. The review concludes by addressing prospects and challenges in the field of oncolytic VACVs, with the aim of promoting further research and application in cancer therapy.